(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Adhesive capsulitis also known as frozen shoulder, pericapsulitis, scapulohumeral periarthritis or check- rein syndrome. The condition usually resolves spontaneously after about 18 months. Adhesive capsulitis is a common musculoskeletal disorder mainly affecting middle aged adults. Also self care activities and occupational activities decreases depends on which shoulder is involved, for instance, self care, grooming, combing hair, eating and dressing are impaired if right shoulder is involved for right handed person, on the other hand dressing and perineal care are hampered if left shoulder is involved. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i1.19423